OPTIMASI KEUNTUNGAN BISNIS BAKPAU MINI HOMEMADE MENGGUNAKAN PROGRAM LINEAR - Rosikin Agus Priandana; Difa Assallam Rizky Maulana, Muhammad Luthfi Fadhillah, Paduloh (Jurnal Ekonomi dan Bisnis, 2025)
Bakpau, derived from the word Baozi. The word Bao means “wrap”, Zi which refers to the word round. Baozi literally means “round wrapper”. It is a soft and delicious food, invented by an important Chinese figure named Zhuge Liang in 220-280 AD, and popularized during the Tang dynasty (618-907 AD) in China. Bakpao is one of China's favorite foods, served as a snack, breakfast, or even a main meal on some occasions. The common filling for buns is pork, however, in Indonesia where the majority of Muslims do not consume pork, the filling of buns has become more varied, such as chicken, beef, chocolate, green beans, and various fruits. Bakpao raw materials such as flour, yeast, sugar, salt, eggs, margarine, and others are a problem; if one of these ingredients is not fulfilled, Bakpao production can be hampered. Therefore, it is important to know what factors can hinder production.